Lower Lip reconstruction using Gillies fan flap - ملحم, فراس (Latakia University Journal -Medical Sciences Series, 2022)
Lips have important aesthetic and functional roles. The lower lip defects may result from a variety of pathologies such as vascular anomalies, burns, trauma, and tumors. Squamus cell carcinoma constitutes 90% of all malignant oral tumors. The lower lip is affected far more frequently than the upper lip. Resection due to squamous cell carcinoma (SCC) is the most common cause of the lower lip defects. Various reconstruction techniques for lower lip defects have been described in the literature.The mmost important factoris the size of lower lip defect for determining the reconstructive method to be employed. Small and medium size defects (up to 80% of the lower lip) may be reconstructed by primary repair and local flaps. The reconstruction of the large size defects (more than 2/3 of the lower lip) is a surgical challenge, because this reconstruction is necessary for oral competence and aesthetic appearance. One of these techniques is Gillies fan flap. In this study Iwe interduce our outcome of 10 performed lower lip reconstruction. All these patients suffered from defects of the lower lip due to squamous cell carcinoma excision. The patients underwent surgery using the proposed surgical technique between 2019 and 2021 in Tishreen University Hospital in Lattakia, Syria. Patients ranged from 46 to 76 years (mean 61 years). Most of the patients were males (seven). We have found this procedure to be reliable, technically easy, and esthetically acceptable. The aesthetic and functional effect of treatment was assessed by the surgeon and the patient. The functional and aesthetic results were satisfactory. No complication is observed in the postoperative period. The sphincter function for normal eating and salivary retain was reestablished. No microstomy was seen and insertion of artificial dentition was possible.